Urgensi Perlindungan Saksi dalam Undang-Undang Nomor 13 Tahun 2006 - Edi Yuhermansyah (Legitimasi: Jurnal Hukum Pidana dan Politik Hukum, 2012)
Protection of witnesses is not based on charity law enforcers, but a right guaranteed by law. Government with members of the legislature has enacted a law on protection of witnesses and victims. The impact of the birth of this legislation to guarantee the physical protection of witnesses from threats and protection of freedom of the witness to ensure the information it conveys no intervention from certain parties. Guarantee the protection of witnesses to be strong after the birth of the witness and victims protection agency is given authority to handle the implementation of protection, the protection of policy-making and supervision. Although this form of protection provided in the statute has not been given guarantees legal protection that is always necessary witness in the face of serious criminal cases.